The Undergorund city and its role in the Urban Mobility - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2008)
The indoor city is a fundamental element in the urban structure; above all in the great cities it assumes strong urban planning connotations because the underground represents an important resource and its employment can have considerable consequences on the urban performance. Some cities, with more hard climate, have designed underground cities with some complex functions; examples are Montreal, Toronto and other cities of North America. In the Western Europe’s cities the notion and the realizations of the underground cities are related with the building of mobility infrastructures as metropolitan networks, underground railway links, road tunnels, car parks. Their aim is the reduction or the removal from the surface of traffic share and the transformation of wide parts of the city in green areas or in more high quality urban environment. Anyway it is possible to maintain that the use of the underground spaces is a common experience in the urban life. The paper analyses some of the main factors in the building of urban pedestrian spaces; the costs and the benefits of the use of underground spaces are linked with the psychological aspects of the use of these spaces and with some main elements in the patterns of the paths. A second part of the paper shows some case-studies, pointing out the different necessities that have driven to the choice. In a specific focus is analysed the case of Montreal, archetype of the underground city.